International and Intercultural Management Research: What's Next? - Earley, P. Christopher; Singh, Harbir (Academy of Management Journal, 1995)
The 1994 Special Research Forum on International and Intercultural Management Research represents an effort to create a better understanding of problems and opportunities in international and intercultural research. Our focus in this forum is to advance international and intercultural research through the presentation of outstanding work using sophisticated new methodologies and research styles to address questions of global business. In our introductory comments, we define international and intercultural research and present a conceptual framework for understanding trade-offs that arise in conducting international research. Next, we describe a number of new avenues for international and intercultural management research. Finally, we give an overview of the articles included in this forum and integrate them into our general framework.